Biofeedback in psychiatric and psychological clinical practice - Julita Poleszak; Przemysław Szabat; Marta Szabat; Grzegorz Boreński; Magdalena Wójcik; Joanna Milanowska (Kazimierz Wielki University, 2019)
Introduction: Biofeedback (BFB) is about improving conscious control over emotional states and some physiological activities. It is a non-invasive, painless and completely safe technique of self-regulation of the body and mind through psychophysiology. The aim of the study: The aim of this article was to present the effects of Biofeedback therapy in psychiatric and psychological clinical situations Material and method: Standard criteria were used to review the literature data. A search of articles was carried out in the PubMed and Google Scholar database. Description of the state of knowledge: Biofeedback is a promising form of behavioral therapy. It can support the work of the mind in healthy people and intensify the treatment of many psychological and psychiatric conditions. The analysis of the research shows that the effectiveness of BFB therapy is high in conditions such as: anxiety disorders, increased stress levels, ADHD, depressive disorders, and insomnia. Summary: The versatile effectiveness of BFB should therefore lead clinicians to encourage this form of therapy during therapeutic treatment of their patients.